2006
DOI: 10.1891/cmj-v7i4a002
|View full text |Cite
|
Sign up to set email alerts
|

Care Managers’ Time Use: Differences Between Community Mental Health and Older People’s Services in the United Kingdom

Abstract: Since the community care reforms of the early 1990s, care management in the United Kingdom has become the usual means of arranging services for even the most straightforward of social care needs. This paper presents data from a diary study of care managers' time use, from a sample of social services commissioning organizations representing the most common forms of care management practiced in England at the end of the 20th century. It compares the working practices of care managers in community mental health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 20 publications
1
35
1
1
Order By: Relevance
“…It would have been desirable to have captured the characteristics of respondents and non-respondents, but the study team was advised that collecting personal information about respondents would be likely to decrease the response rate. Caution should be exercised in generalising the study's findings therefore, although, interestingly, the results are not greatly different from those reported in other work that has utilised a similar classification, [39][40][41][42]76 while the mix of services for older people with mental Models of Care health problems in the study area appeared typical of services nationwide. 34 At least some data were recorded retrospectively, as the pressures of work obliged busy practitioners to wait until the day' s end before completing schedules.…”
Section: Limitationsmentioning
confidence: 38%
See 2 more Smart Citations
“…It would have been desirable to have captured the characteristics of respondents and non-respondents, but the study team was advised that collecting personal information about respondents would be likely to decrease the response rate. Caution should be exercised in generalising the study's findings therefore, although, interestingly, the results are not greatly different from those reported in other work that has utilised a similar classification, [39][40][41][42]76 while the mix of services for older people with mental Models of Care health problems in the study area appeared typical of services nationwide. 34 At least some data were recorded retrospectively, as the pressures of work obliged busy practitioners to wait until the day' s end before completing schedules.…”
Section: Limitationsmentioning
confidence: 38%
“…All social workers, social care workers, community mental health nurses (CMHNs) and community support workers who primarily worked with older people were asked to complete a specially designed diary schedule adapted from previous research [39][40][41][42] to reflect local practice on each working day within a 1-week period in April/May 2004. This involved inserting a code for the activity in which they had been predominantly engaged for each 30-minute period from a list of 45 activities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this assistance was mostly unable to be reciprocated due to the nursing specific interventions required (Cosgrave et al ). While the internal coordination of care role has previously been documented in nursing literature, the findings of this study will assist services to quantify this role and to determine the number of nursing full time equivalent community appointments required by the service (Burnard et al ; Henderson et al ; Jacobs et al ). The need for further research to compare workload allocation and complexity of CMHNs with other community mental health professionals is also apparent to the ongoing composition of effective community teams.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research studies have suggested that an administrative type of care coordination for the purpose of providing information and advice in the short-term predominates in England. 32,38,39 Joint working between health and social care. A lack of service integration has been associated with fragmented poorly coordinated services at the level of the individual, with delays or failure of service delivery.…”
Section: Measures Of Care Coordinationmentioning
confidence: 99%